2014
DOI: 10.5539/gjhs.v7n3p8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Amsel's Clinical Criteria for Diagnosis of Bacterial Vaginosis

Abstract: Introduction:Bacterial vaginosis (BV) is one of the most prevalent infections in women of reproductive age. Amsel’s criteria and Nugent scoring system are among the most commonly used diagnostic methods. Although Nugent scoring system is considered the gold standard for diagnosing BV, it is time consuming and costly, and its interpretation needs lab equipment and experts. Hence, most physicians are inclined to use simpler clinical criteria that are yet accurate instead. The present study aimed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 16 publications
(21 reference statements)
2
48
2
2
Order By: Relevance
“…And Amsel criteria could be as good as Nugent scoring system at diagnosing this infection. 14 In present study authors considered Nugent's criteria as gold standard and found that Amsel's criteria had positive predictive value = 88.88%, negative predictive value = 79.67%, sensitivity = 71.11% and specificity = 92.73%.…”
Section: Discussionmentioning
confidence: 66%
“…And Amsel criteria could be as good as Nugent scoring system at diagnosing this infection. 14 In present study authors considered Nugent's criteria as gold standard and found that Amsel's criteria had positive predictive value = 88.88%, negative predictive value = 79.67%, sensitivity = 71.11% and specificity = 92.73%.…”
Section: Discussionmentioning
confidence: 66%
“…These four patients all received the commercially available lactic acid pessary after metronidazole therapy at visit 3 and visit 4. A Nugent score of >6 was used to determine BV status since it is considered the gold standard for BV diagnosis ( 55 ) (see Data Set S1 , sheet 1, in the supplemental material). The BV status at visit 5 was determined by Amsel criteria as there was no Nugent score available at that time point.…”
Section: Methodsmentioning
confidence: 99%
“…Closely related results were obtained by Gad et al, (2014) who found that Amsel's criteria had a sensitivity of 88% and a specificity of 89.6% for the diagnosis of BV compared to the Nugent score. However, higher sensitivity (91% and 91%) and specificity (99% and 91%) for Amsel's criteria were reported by Bradshaw et al, (2005) and Mohammadzadeh et al, (2015), respectively. On the other hand, in the studies of Beverly et al, (2005), Dadhwal et al, (2010), Modak et al, (2011), Khatoon et al, (2013) and Taj et al, (2014), a much lower sensitivity (37%, 51.2%, 66.7%, 69%, and 68.3% respectively) with a higher specificity (99%, 98%, 94.7%, 93.1%, and 97.1% respectively) were reported.…”
Section: Diagnostic Performance Of the Amsel's Criteria Compared To Nmentioning
confidence: 71%